Planning Support Systems for Sustainable Urban Development - Geertman, Stan.; Toppen, Fred.; Stillwell, John.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book collects a selection of the best articles presented at the CUPUM (Computers in Urban Planning and Urban Management) conference, held in the second week of July 2013 in Utrecht, the Netherlands. The articles included were selected by external reviewers using a double blind process.
Keywords: Geography; Geographical information systems; Regional planning; Sustainable development; Geography; Geographical Information Systems/Cartography.; Sustainable Development; Landscape/Regional and Urban Planning